Eficacia de los implantes Subdérmicos versus anticonceptivos combinados, efectos adversos y manejo en usuarias atendidas en el Hospital Universitario de Motupe, periodo enero - junio del 2013. - Chávez Guamán, Angel Cornelio (2013)
Objective: To determine the efficacy of subdermal implants versus combined contraceptives, adverse effects and their management. Materials and methods: observational, descriptive, prospective and analytical trial. Hormonal injectable, oral users were included and implant; the efficacy and adverse effects were determined. Results: 300 users, 30% of oral hormonal (n=90), 24% of injectable monthly (n=72) and 46% surveyed of implant subdermal (n=138). The average time was 12 months, age of 27.9 years. Adverse effects were presented in 83.33% (n=115) of users of implant, 44,44% (n=40) of hormonal oral and 58,33% (n=42) of injectable. The effectiveness showed to implant an index of 0, for hormonal Pearl oral 0.3 and 0.1 inyectables. Conclusion: The effectiveness of three contraceptives is appropriate, obtaining that subdermal implants are effective in 100%, followed with a 98, 61% injectable contraceptives, and finally combined oral contraceptives with 96, 66%. Adverse effects are high users of implant. The hormonal oral and injectable monthly are effective and safe contraceptive methods, with fewer adverse effects than the implant You can conclude that the use of hormonal contraceptives has important adverse goods in the first months of use, with reduction of the same ones as it lapses the time.